Photolabile Protecting Groups Based on the Excited State Meta Effect: Development and Application. (1st September 2022) - Wang, Pengfei; Lim, Chaeeun
Abstract: This review focuses on utilization of the excited state meta effect (ESME) in the development of photolabile protecting groups (PPGs). Structurally simple ESME‐based PPGs for release of various functional groups (such as carbonyl, hydroxyl, carboxyl, amino and thiol groups) are discussed. Examples that demonstrate the appealing advantages of these new PPGs are provided, including their efficient release of "poor" leaving groups such as hydroxyl or amino group directly instead of in their respective carbonate or carbamate form. Applications of these PPGs in synthesis, release of biologically important molecules, materials science and biomedical engineering are also described. Abstract : Structurally simple photolabile protecting groups based on the excited state meta effect (ESME) release carbonyl, hydroxyl, carboxyl, amino and thiol groups effectively. They can find various applications in synthesis, release of biologically important molecules, materials science and biomedical engineering.